The role of additive manufacturing technology in reducing the costs of dental manufacturing: An applied study at the Dental Manufacturing and Orthodontics Center \ Bab Al-Muadham (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The current environment is witnessing rapid developments as a result of the developments in the surrounding environment, which led to the necessity of adopting modern methods and approaches that are compatible with the requirements of the current environment to provide high-quality information to decision-makers. The research aims to calculate the cost of dental manufacturing by applying modern technologies, especially additive manufacturing technology, in order to reduce costs for the unit in question. To achieve the research objectives, the approved costs were evaluated in light of the current reality by identifying the costs that were not calculated in the dental industry and analyzing them in the unit in question, and then reducing costs in light of additive manufacturing technology (AM) in that unit by calculating the cost based on activities in calculating costs and then in light of additive manufacturing technology (AM) to improve the quality of dental manufacturing and reduce costs and time, thus achieving the research objective. Many conclusions were reached, the most important of which is that calculating the cost of dental manufacturing based on additive manufacturing technology (AM) contributes to reducing costs in the unit in question. Consequently, many recommendations were reached, the most important of which is for economic units specialized in the dental industry; relying on additive manufacturing technology (AM) for the purpose of reducing costs.